2017
DOI: 10.3758/s13428-016-0841-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric validation of a child Racial Attitudes Index (RAI)

Abstract: The Racial Attitudes Index (RAI) measures a child's racial attitudes. Designed for children aged 5-9 years, the RAI is delivered over the Internet using Audio Computer Assisted Self-Interviewing (ACASI). Unlike traditional binary forced-choice instruments, the RAI uses an expanded response format permitting a more nuanced understanding of patterns of children's racial attitudes. In addition to establishing psychometric evidence of the RAI technical adequacy, hypotheses about RAI item response patterns were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In their scientific literature analysis about ethnic prejudices, Clark et al, (2017) mentioned studies that had shown tendencies of light-skinned boys and girls, from kindergarten to elementary school, to positively rate subjects or groups with their skin colour and to evaluate those who had dark skin tones negatively (Williams & Morland, 1976;Aboud, 1988;Katz & Kofkin, 1997;Bernstein et al, 2000;Baron & Banaji, 2004;McGlothlin & Killen, 2006;Gibson et al, 2015), especially when the former had no direct contact with the latter (Radke & Sutherland, 1949;George & Hoppe, 1979;Jarrett, 1981). However, several studies have shown that older girls and boys develop positive attitudes towards each other (Katz & Zalk, 1978;Cameron et al, 2007;Verkuyten & De Wolf, 2007), having a greater capacity for «reconciliation», that is, the ability to recognize preferences other than one's own as equally valid and just, compared to younger girls and boys (Johnson & Aboud, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In their scientific literature analysis about ethnic prejudices, Clark et al, (2017) mentioned studies that had shown tendencies of light-skinned boys and girls, from kindergarten to elementary school, to positively rate subjects or groups with their skin colour and to evaluate those who had dark skin tones negatively (Williams & Morland, 1976;Aboud, 1988;Katz & Kofkin, 1997;Bernstein et al, 2000;Baron & Banaji, 2004;McGlothlin & Killen, 2006;Gibson et al, 2015), especially when the former had no direct contact with the latter (Radke & Sutherland, 1949;George & Hoppe, 1979;Jarrett, 1981). However, several studies have shown that older girls and boys develop positive attitudes towards each other (Katz & Zalk, 1978;Cameron et al, 2007;Verkuyten & De Wolf, 2007), having a greater capacity for «reconciliation», that is, the ability to recognize preferences other than one's own as equally valid and just, compared to younger girls and boys (Johnson & Aboud, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Clark et al (2017), the PRAM II (Preschool Racial Attitude Measure II) developed by Williams and Morland (1975), and the Katz-Zalk Projective Prejudice Test (KZPP) developed by Katz and Zalk (1976) have been two of the most commonly used tools for evaluating explicit ethnic attitudes over time. Using both methods, the administrator reads short stories characterized by positive or negative actions and adjectives.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations